2013
DOI: 10.1161/circinterventions.113.000529
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Outcomes After Transcatheter Aortic Valve Implantation

Abstract: Studies were initially screened at the level of title and abstract, and then full-length reports were retrieved for detailed evaluation. Two authors independently selected articles according to prespecified inclusion and exclusion criteria. Articles were included if they (1) reported Background-There were considerable discrepancies with regard to sex-related differences in complications and prognosis after transcatheter aortic valve implantation. Methods and Results-The Cochrane library and PubMed online datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 44 publications
8
40
0
2
Order By: Relevance
“…The results of the present meta-analysis are in line with the recent work of Zhao and colleagues [18], although the two meta-analyses mainly differ in the selection criteria applied. Our meta-analysis included only studies reporting adjusted midterm mortality to understand in a more accurate way the independent role of gender after TAVI.…”
Section: Commentsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present meta-analysis are in line with the recent work of Zhao and colleagues [18], although the two meta-analyses mainly differ in the selection criteria applied. Our meta-analysis included only studies reporting adjusted midterm mortality to understand in a more accurate way the independent role of gender after TAVI.…”
Section: Commentsupporting
confidence: 90%
“…A recent meta-analysis on the same topic reported better short-term and midterm survival for women. One of the most intriguing questions that the previously cited report left unsolved, however, is the effect of female gender itself on outcomes after TAVI: actually, the included studies were not adjusted for confounding variables [18]. Thus, we decided to perform a meta-analysis of observational results evaluated after adjustment for clinical and procedural features to clarify the independent prognostic role of gender in patients undergoing TAVI.…”
mentioning
confidence: 99%
“…This is probably related to the increased incidence of vascular complications in patients with smaller arteries. 29,30 None of the vascular complications in this study were attributed to thromboembolic events, and all originated from injury to the artery or occlusion from the large cannula. Patients in shock and on inotropic support also showed a significantly higher incidence of limb ischemia, probably because they were hypoperfused to begin with, and as may be expected, the Impella device was placed for a longer time.…”
Section: Discussionmentioning
confidence: 80%
“…Several previous studies including a recent meta-analysis have suggested better results of TAVR in women, but no clear explanation was found for this sex paradox in the TAVR field. [20][21][22] Female sex is usually associated with smaller aortic annulus, and this study provides further insight into the potential advantages of having a small aortic annulus when receiving a transcatheter valve. On the contrary, a negative impact has been associated with female sex in patients undergoing cardiac surgery including aortic valve replacement in elderly patients.…”
Section: Aortic Annulus Size and Clinical Outcomesmentioning
confidence: 77%